PERANCANGAN NETWORK ATTACHED STORAGE (NAS) MENGGUNAKAN RASPBERRY PI UNTUK USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Cosmas Eko Suharyanto; Algifanri Maulana (LPPM Nusa Mandiri, 2020)
The aim of this study is to design a network attached storage (NAS) that is easy to implement, also in terms of cost, affordable for small and medium businesses. We use Raspberry mini computers as media. Raspberry is very flexible and easy to apply for various needs, especially in the field of networking and IoT. With the Openmediavault as an Operatisng System, we success to turn external hard disks into NAS storage that can be easily configured and adapted to storage needed in an office or Small and Medium Business. Based on the evaluation results of NAS network stability with Raspberry Pi 3, showing good network stability status.